A new species of Amphipyra Ochsenheimer, 1816 (Lepidoptera, Noctuidae) from China - Babics, János; Benedek, Balázs; Saldaitis, Aidas (Zootaxa, 2013)
The genus Amphipyra Ochsenheimer, 1816 has been rife with taxonomic problems including numerous undescribed taxa and cryptic species, due to its circumscribed species-groups and the similarities in genitalia to other member-species. Description of this new Amphipyra species which was first encountered in expeditions to China by V. Siniaev, A. Plutenko and S. Murzin is now facilitated by better comparative material and more extensive professional relationships but the need for further revision of the genus Amphipyra is well recognized. Material for this study was collected in July, 2005 and August, 2011, by using artificial light.Taxonomic nomenclature used in this study were constituted according to taxonomical experts and relevant literature (Draudt 1950; Yoshimoto 1994; Hreblay & Ronkay 1998; Kononenko et al. 1998; Chen 1999; Hreblay & Ronkay 2000; Kononenko 2005; Kononenko & Han 2007).